Isolation and characterization of conformational isomers of N, N′‐bis(3, 5‐dichlorosalicylidene)‐2, 2′‐ethylenedianiline: crystal structure, photoluminescence, and density functional theory calculation. (9th October 2014) - Min, Kil Sik; Kim, Yoon Jae; Ko, Hyun Jin; Kwak, Dae Hyun; Kim, Tae Wook; Shin, Jong Won; Kim, Bong Gon
<x xml:space="preserve">Abstract</x> We have isolated two isomeric solids 1 and 2 of N, N′‐bis(3, 5‐dichlorosalicylidene)‐2, 2′‐ethylenedianiline and characterized by IR, UV/Vis, X‐ray powder diffraction, thermogravimetric analysis/differential thermal analysis, and X‐ray crystallography. Although the solids are same formulas, each shows different colors and crystal structures. Orange solid (1) shows endo conformation while yellow solid (2) exhibits exo form depending on packing modes. UV/Vis spectra of 1 and 2 appear very similar patterns in the solid state; however, the bands of 1 are slightly red‐shifted compared with those of 2. 1 displays a strong fluorescent emission band at 582 nm while 2 shows an intense fluorescent signal at 563 nm. The charge density populations of 1 and 2 have been studied by computational simulations using density functional theory at pbe1pbe/6‐311G** level. The calculated highest occupied molecular orbital and lowest unoccupied molecular orbital energies of 1 and 2 confirm that charge transfer occurs within the organic molecules. The energy difference of HOMO‐LUMO in 1 is smaller slightly than that of 2 about 0.05 eV ( 17 nm). Copyright © 2014 John Wiley & Sons, Ltd.